IMPROVING KNOWLEDGE ABOUT CLEAN AND HEALTHY LIVING BEHAVIORS IN CHILDREN - Kusuma Wijaya Ridi Putra; Sri Wahyuni Ahmad; Leli Anggita; Marita Milenia; Nafarotul Ilmiyah; Apri Wijaya; Tita Hiyasti (Community Service Journal of Indonesia, 2020)
Health promotion activities on clean and healthy living behavior at the Elementary School of Rangkah Kidul, Sidoarjo is one form of community service in the form of counseling aimed at increasing children's knowledge about the importance of clean and healthy living behaviors in daily activities. The activity was carried out on November 18, 2019 at the Elementary School of Rangkah Kidul, Sidoarjo. The target is the students of the Elementary School of Rangkah Kidul, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 3 weeks before the activity is carried out, starting from determining the theme of counseling to submitting permits to the parties concerned. As a form of evaluation, the activity was attended by 40 students from class III of the Elementary School of Rangkah Kidul, Sidoarjo. Participants participated in the activity with great enthusiasm, health promotion activities were able to run on time and smoothly. Keywords: Clean and healthy lives, washing hand, health behaviors knowledge.